2022
DOI: 10.1029/2021wr030921
|View full text |Cite
|
Sign up to set email alerts
|

Hydrological Basis of Different Budyko Equations: The Spatial Variability of Available Water for Evaporation

Abstract: Based on observations from a large number of catchments, Budyko (1974) hypothesized that climate aridity index (i.e., the ratio between mean annual potential evaporation and precipitation, ๐ด๐ด ๐ธ๐ธ ๐‘๐‘ ๐‘ƒ๐‘ƒ ) is the dominant controlling factor of evaporation ratio (i.e., the ratio between mean annual evaporation and precipitation, ๐ด๐ด ๐ธ๐ธ ๐‘ƒ๐‘ƒ ). Thereafter, the function for the relationship between evaporation ratio and climate aridity index is named as Budyko curve or equation. The impacts of other fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 84 publications
0
4
0
Order By: Relevance
“…When the net effect of groundwater flux across the watershed boundary and human impacts are negligible, WAI becomes the climate aridity index. The Budykoโ€type curve corresponding to Gamma distribution for describing the spatial distribution of available water for ET (Yao & Wang, 2022) is illustrated as follows: normalEnormalTnormalAnormalWnormalEnormalT=1normalฮ“(k)[]kโˆ’1ฮณ()k+1,kETPnormalAnormalWnormalEnormalT+ETPnormalAnormalWnormalEnormalTnormalฮ“()k,kETPnormalAnormalWnormalEnormalT $\frac{\mathrm{E}\mathrm{T}}{\mathrm{A}\mathrm{W}\mathrm{E}\mathrm{T}}=\frac{1}{{\Gamma }(k)}\left[{k}^{-1}\gamma \left(k+1,k\frac{{\mathrm{E}\mathrm{T}}_{P}}{\mathrm{A}\mathrm{W}\mathrm{E}\mathrm{T}}\right)+\frac{{\mathrm{E}\mathrm{T}}_{P}}{\mathrm{A}\mathrm{W}\mathrm{E}\mathrm{T}}{\Gamma }\left(k,k\frac{{\mathrm{E}\mathrm{T}}_{P}}{\mathrm{A}\mathrm{W}\mathrm{E}\mathrm{T}}\right)\right]$ where normalฮ“(k) ${\Gamma }(k)$ is the gamma function; ฮณ()k+1,kPEp $\gamma \left(k+1,\frac{k}{P}{E}_{p}\right)$ is the lower incomplete gamma function, and normalฮ“()k,kPEp ${\Gamma }\left(k,\frac{k}{P}{E}_{p}\right)$ is the upper incomplete gamma function; and k $k$ is catchmentโ€specific parameter relating to factors other than WAI that affect GWET ratio. The functional forms for Budyko curves are dependent on the distribution functions for the spatial variability of available water to ET (Wang, 2018; Yang et al., 2008).…”
Section: Methodsmentioning
confidence: 99%
“…When the net effect of groundwater flux across the watershed boundary and human impacts are negligible, WAI becomes the climate aridity index. The Budykoโ€type curve corresponding to Gamma distribution for describing the spatial distribution of available water for ET (Yao & Wang, 2022) is illustrated as follows: normalEnormalTnormalAnormalWnormalEnormalT=1normalฮ“(k)[]kโˆ’1ฮณ()k+1,kETPnormalAnormalWnormalEnormalT+ETPnormalAnormalWnormalEnormalTnormalฮ“()k,kETPnormalAnormalWnormalEnormalT $\frac{\mathrm{E}\mathrm{T}}{\mathrm{A}\mathrm{W}\mathrm{E}\mathrm{T}}=\frac{1}{{\Gamma }(k)}\left[{k}^{-1}\gamma \left(k+1,k\frac{{\mathrm{E}\mathrm{T}}_{P}}{\mathrm{A}\mathrm{W}\mathrm{E}\mathrm{T}}\right)+\frac{{\mathrm{E}\mathrm{T}}_{P}}{\mathrm{A}\mathrm{W}\mathrm{E}\mathrm{T}}{\Gamma }\left(k,k\frac{{\mathrm{E}\mathrm{T}}_{P}}{\mathrm{A}\mathrm{W}\mathrm{E}\mathrm{T}}\right)\right]$ where normalฮ“(k) ${\Gamma }(k)$ is the gamma function; ฮณ()k+1,kPEp $\gamma \left(k+1,\frac{k}{P}{E}_{p}\right)$ is the lower incomplete gamma function, and normalฮ“()k,kPEp ${\Gamma }\left(k,\frac{k}{P}{E}_{p}\right)$ is the upper incomplete gamma function; and k $k$ is catchmentโ€specific parameter relating to factors other than WAI that affect GWET ratio. The functional forms for Budyko curves are dependent on the distribution functions for the spatial variability of available water to ET (Wang, 2018; Yang et al., 2008).…”
Section: Methodsmentioning
confidence: 99%
“…The shape parameter value for a specific basin will vary based on its climatological (ET P , P) and hydrological (ET, baseflow, streamflow) characteristics (Equation 1). The shape parameter ฯ‰ has been used extensively as an indicator to reflect the characteristics of a basin such as climate (Feng et al, 2012(Feng et al, , 2015Xu et al, 2013), vegetation (Li et al, 2013), topography (Yang et al, 2014;Bai et al, 2020), and combinations of the above mentioned parameters (Milly, 1993(Milly, , 1994Zhang et al, 2001Zhang et al, , 2004Porporato et al, 2004;Donohue et al, 2007;Yang et al, 2007Yang et al, , 2009Abatzoglou and Ficklin, 2017;Yao and Wang, 2022). For example, Li et al (2013) found a strong correlation between ฯ‰ and annual vegetation coverage in 26 major global river basins.…”
Section: The Budyko Shape Parameter ฯ‰mentioning
confidence: 99%
“…The model has been widely used in land surface hydro-thermal coupling simulation and evolution mechanism analysis (Yang et al, 2021;Li and Quiring, 2022). Several methods have been proposed for studying the Budyko hypothesis, among which the p-fu (Xing et al, 2018;Ning et al, 2019), Choudhury-yang (Zhang et al, 2018;Meng et al, 2019;Hou et al, 2022), and Wang and Tang (Yao and Wang, 2022) formulas are commonly used. In the Budyko formula, the underlying surface parameter n reflects the influence of catchment characteristics and determines the shape of the Budyko curve.…”
Section: Introductionmentioning
confidence: 99%